STATUS HUKUM ANAK DI DALAM KANDUNGAN SEBAGAI AKIBAT PUTUSNYA PERKAWINAN ORANG TUA - Welza Angelia Wattimena; Inri Januar; Nanin Koeswidi Astuti (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
In Indonesia, there are still many problems regarding the custody of children to whom it is appropriate to give, this happens because of the breakup of the parents' marriage which causes the maintenance of child custody to be contested. The formulation of the problem in this thesis is whether a child in the womb can be the object of custody due to the breakup of the parents' marriage and how the judge's application of law to the child in the womb is related to the child's custody rights due to the breakup of the parents' marriage (Decision Study Number xxx/ Pdt.G/2021/PN Prp). The research method used is normative legal research with a statutory approach, analytical approach and case approach. The type of data used is the Marriage Law, and a set of regulations related to this research, and obtained from law books or journals or other literature. From the results of this research, it can be concluded that unborn children cannot be used as objects of child custody rights because they are legal subjects who deserve protection as citizens for their desired interests. The decision to determine custody of an unborn child before birth can give rise to legal uncertainty.